1991
DOI: 10.1071/sr9910455
|View full text |Cite
|
Sign up to set email alerts
|

Rain energy and soil amendments effects on infiltration and erosion of three different soil types

Abstract: The effect of rain kinetic energy and soil amendments on infiltration and erosion from three Israeli soils was studied using a drip-type simulator. The soil samples were from the top layer (0-250 mm depth) of cultivated fields differing in their texture, specific surface area and lime content. Three kinetic energies of raindrops were obtained by varying heights of fall (h = 0.4, 1-0 and 1.6 m) of 3 mm diameter drops. The soil types studied were Typic Chromoxerert, Typic Rhodoxeralf and Calcic Haploxeralf. Soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…Shainberg et al (1990Shainberg et al ( , 1992 applied three rates of PAM on dry soil in a smalltray laboratory study prior to sprinkling in a rainfall simulator and reported that 20 kg ha -I PAM best maintained high-infiltration rates. Smith et al (1990) and Levin et al (1991), in similar studies, found that 20 kg ha -I of PAM increased infiltration and greatly reduced runoff and erosion. Peterson et al (2001Peterson et al ( , 2002) also found in small-tray studies that PAM sprayed on soil prior to simulated rainfall reduced runoff and erosion.…”
Section: Sprinkler Irrigationmentioning
confidence: 77%
See 1 more Smart Citation
“…Shainberg et al (1990Shainberg et al ( , 1992 applied three rates of PAM on dry soil in a smalltray laboratory study prior to sprinkling in a rainfall simulator and reported that 20 kg ha -I PAM best maintained high-infiltration rates. Smith et al (1990) and Levin et al (1991), in similar studies, found that 20 kg ha -I of PAM increased infiltration and greatly reduced runoff and erosion. Peterson et al (2001Peterson et al ( , 2002) also found in small-tray studies that PAM sprayed on soil prior to simulated rainfall reduced runoff and erosion.…”
Section: Sprinkler Irrigationmentioning
confidence: 77%
“…PAM, however, limits aggregate disruption caused by water drop impacts. Smith et al (1990) and Levin et al (1991) reported that the relative effect of PAM on aggregate stability increased with increasing kinetic energy of the water drops. This may be related to the finding that only the outer surfaces of aggregates are stabilized by PAM treatment due to the relatively shallow penetration of the macromolecule (Ben-Hur and Keren, 1997; Malik and Letey, 1991).…”
Section: Sprinkler Irrigationmentioning
confidence: 99%
“…Greater amounts of PAM are needed to control sprinkler irrigation induced soil erosion, and results generally are not as dramatic. Spraying a high PAM concentration liquid on the soil at 20 kg PAM ha-1 before simulated rainfall significantly reduced runoff and soil erosion (Ben-Hur, 1994;Levin et al, 1991). Zhang and Miller (1996) also used a high concentration PAM solution at 15 and 30 kg ha-1 and measured increased infiltration and decreased erosion, but the effects decreased with subsequent simulated rains.…”
mentioning
confidence: 99%
“…However, runoff can be a problem because the water application rate often exceeds the soil infiltration rate (Gilley and Mielke, 1980;Kincaid et al, 1969). Runoff on a center pivotirrigated field generally does not flow from the field, but ponds and infiltrates in low areas within the field, resulting in reduced irrigation uniformity.Several laboratory studies have shown that spraying concentrated PAM solutions [500 mg L-1 (0.05%)] on the soil surface at rates equal to or greater than 20 kg ha-1 (18 lb a-1 ) increased final infiltration rate and decreased soil erosion during simulated rainfall (Ben-Hur and Keren, 1997;Levy and Agassi, 1995;Levin et al, 1991;Smith et al, 1990). Spraying PAM directly on the soil, however, requires a large volume of solution (i.e., > 5000 L ha-1 or 530 gal a-1 ) or a high viscosity solution.…”
mentioning
confidence: 99%
“…Several laboratory studies have shown that spraying concentrated PAM solutions [500 mg L-1 (0.05%)] on the soil surface at rates equal to or greater than 20 kg ha-1 (18 lb a-1 ) increased final infiltration rate and decreased soil erosion during simulated rainfall (Ben-Hur and Keren, 1997;Levy and Agassi, 1995;Levin et al, 1991;Smith et al, 1990). Spraying PAM directly on the soil, however, requires a large volume of solution (i.e., > 5000 L ha-1 or 530 gal a-1 ) or a high viscosity solution.…”
mentioning
confidence: 99%